The Political Communication Strategy of the Presidential Campaign Team Jokowi-Ma'ruf Amin to Win the Support of the Ummah Islam in the 2019 Election in North Sumatra - Hasyimsyah Nasution; Syukur Kholil; Muhammad Idris (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to analyze the communication patterns of President Jokowi-Ma'ruf's campaign team in the 2019 elections in North Sumatra, the communication management of the campaign team, the response of the voters, and the results achieved by the campaign team. The data sources consisted of primary data, namely from the North Sumatra regional campaign team and secondary data from various books, documents, journals, articles, websites and others related to this research. The main informants were the campaign team which was determined purposively in accordance with the research objectives. Besides that, the community also distributed questionnaires to the voters for the Jokowi-Ma'ruf Amin presidential candidate in several cities and districts, namely Medan, Tebing Tinggi, Simalungun, and Tapanuli Tengah as a form of representation from the regions in North Sumatra because of the diversity of ethnicities, cultures, and religion. The results of the study indicate that the communication pattern of President Jokowi-Ma'ruf Amin's regional campaign team in North Sumatra is carried out in broad lines through two forms, namely direct communication with the community and indirect communication or by using mass media. The delivery of infrastructure development work programs to the campaign masses received a response from the voting public. Campaigns through the approach and involvement of religious leaders can also attract sympathy from the voters. The voters for the Jokowi-Ma'ruf presidential candidate in North Sumatra generally answer because of the figure of the presidential candidate. Meanwhile, the position of Kiyai Haji Ma'ruf Amin as a vice presidential candidate is a factor that can influence or increase the electability of Muslims in determining the victory of a presidential candidate.